If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -35 + -3x = 9x + 19 Reorder the terms: -35 + -3x = 19 + 9x Solving -35 + -3x = 19 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -35 + -3x + -9x = 19 + 9x + -9x Combine like terms: -3x + -9x = -12x -35 + -12x = 19 + 9x + -9x Combine like terms: 9x + -9x = 0 -35 + -12x = 19 + 0 -35 + -12x = 19 Add '35' to each side of the equation. -35 + 35 + -12x = 19 + 35 Combine like terms: -35 + 35 = 0 0 + -12x = 19 + 35 -12x = 19 + 35 Combine like terms: 19 + 35 = 54 -12x = 54 Divide each side by '-12'. x = -4.5 Simplifying x = -4.5
| 130=2x-y | | -2(x+9)+91=13+24 | | 2(111)=d | | 7x+26=4x+77 | | 4x-6x=7 | | 34-2x=7x+21 | | -3x^2-4x+1=0 | | 3-8s=-29 | | 4x+y+x+3y=180 | | x^2-6x+9=2 | | 66x+35=25 | | (7-8)+17= | | 10x-28=4x+22 | | x^2=x+4 | | 97x+66=10 | | p(x)=-2x^2+60x-25 | | 169-2x=25x+22 | | 86x-53=9 | | 90-2x=4x+24 | | 4x^2+48x+27=0 | | y+9y+5=15 | | 60x-35=8 | | 18x-7i=3(6x-7u) | | 37x+50=9 | | 14x+4x^2=78 | | 14x+4x=78 | | 3z+6=4z^2+4z+1 | | 3(2-x)=3018 | | 2d+3=-10+d | | 2x^2+7x=39 | | 5c+5=4c+4 | | 200x=2x |